Investigating Intrinsic and Extrinsic Factors Influencing English Self-Learning Motivation Among Indonesian University Students - Andi Farid Baharuddin; Dwi Rezki Hardianto Putra Rustan (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
English has been widely known as a global lingua franca. By mastering English, it enables students to build good communication on a global scale and assists them to express their interests in many sectors such as economy, politics, culture, and education (Pennycook, 2025). These interests definitely influence students’ motivation in studying English. Therefore, this research aimed to investigate the discourse of students’ self-learning motivation in English by exploring both motivational factors, i.e., intrinsic and extrinsic factors. In doing this scientific work, the researchers applied Cresswell's (2016) convergent parallel mixed-method design that variedly provided both qualitative and quantitative data. With these various data, it helped the readers to comprehend the research explanation. The results demonstrated that both intrinsic and extrinsic factors have contributive aspects in maintaining students’ motivation in English learning. For instance, for the intrinsic factors, 60% of students are motivated to study English to gain a job, while self-confidence development and the pursuit of gaining a good academic score are equally 20%. In addition, the extrinsic factors consist of several conditions, i.e., educational (i.e., provided material with 13.3% voters and technological devices (TD) as learning facilities with 73.3% voters) and social (family support with 13.3% voters) conditions. Although intrinsic factors (66.7%) exert a more significant influence than extrinsic factors (33.3%), it is undeniable that both substantially impact students' self-learning motivation in English. Therefore, by investigating both of these factors, the researchers expected that it would help the educators to design the effective teaching curriculum in the English course.